Implementation of Knowledge Integration in Islamic Higher Education - Suwendi, Suwendi; Mesraini, Mesraini; Azka, Farah Layli; Gama, Cipta Bakti (Jurnal Pendidikan Islam, 2024)
Knowledge integration in higher education institutions is a crucial topic for advancing academic and practical outcomes. This study investigated the implementation of knowledge integration at UIN Jakarta, focusing on its policies, practices, and philosophical foundations. Using qualitative methods such as document analysis and interviews, the research examines how UIN Jakarta integrates religious and secular knowledge within its academic framework. The findings reveal that UIN Jakarta has established a robust philosophical basis for knowledge integration, emphasizing an open-minded and dialogic approach to learning. Additionally, the university has enacted various policies at both institutional and faculty levels to support this initiative. However, limitations include the lack of comprehensive policies across all faculties and minimal emphasis on community service programs related to knowledge integration. In conclusion, this study provides valuable insights into the challenges and opportunities associated with knowledge integration in Islamic higher education institutions, highlighting the need for further research and evidence-based practices to enhance these efforts.